ANALYSIS AND EVALUATION OF GENETIC FACTORS IN THE DEVELOPMENT OF CHRONIC DISEASES. - Saud Saleh M Almutairi, Saeed Yousef M. Alghamdi, Raed Sulaiman Almutairi,; Sarah Ibrahim Alqahtani, Abdulrahman Misfer Alqahtani, Khulud Mohammed Hakami, (Chelonian Research Foundation, 2023)
Genetic factors play a significant role in the development of chronic diseases, influencing an individual's susceptibility and response to various environmental factors. Understanding the interplay between genetics and chronic diseases is crucial for advancing personalized medicine and improving patient outcomes. This essay provides an analysis and evaluation of genetic factors in the development of chronic diseases, exploring the current literature and highlighting key findings. The methodology, results, and discussion sections will delve into specific genetic markers associated with common chronic diseases, such as cardiovascular disease, diabetes, and cancer. Ultimately, this essay aims to consolidate the existing knowledge on genetic factors in chronic disease development and emphasize the importance of personalized medicine in disease management.